Comparison of the Elastic–Plastic Indentation Response of MgAl2O4, AlON, and AlN. Issue 4 (28th February 2013) - Muller, Andrea M.; Green, David J.; Pharr, G.
<x xml:space="preserve">Abstract</x> Contact damage in the form of localized cracking and inelastic deformation is of concern in the utilization of ceramics and is often studied using hard indenters; an approach that has spawned the field of indentation mechanics. This approach was taken in the current work to study the penetration resistance at low strain rates of four candidate ceramic armor materials: MgAl2O4 with two grain sizes, AlON and AlN. Spherical indentation was chosen as this allows the elastic–plastic behavior to be studied and the indentation stress–strain curves to be determined. To further quantify these data, the elastic and plastic indentation work contributions were measured. On empirical grounds, it was postulated that the area under the indentation stress–strain curves, termed the indentation strain energy density, was related to the total indentation work could be used to quantify the penetration resistance. As a test of this hypothesis, it was shown that the total indentation work correlated with the strain energy density and acted over a volume similar to that of the stress field. A simple figure of merit, derived from the indentation strain energy density, was suggested as a means to quantify the penetration resistance of materials at low strain rates and to identify the material parameters that control this process.